Proses Penciptaan Komposisi Musik “PEDHOT” untuk Violin dan Piano karya Eki Satria - Eki Satria (Tambur : Journal of Music Creation, Study and Performance, 2021)
This study aims to describe the process of composing music composition through empirical ideas. The author highlights an incident that is often encountered in a concert or string instrument recital, especially the violin, which is an incident in the form of breaking a string during a performance. From this observation, the author has the idea of ??composing a musical composition where the breaking of the strings becomes a conceptual part of a performance. The research method used is a qualitative method with a descriptive approach through three stages, namely literature study, observation and experimentation. In the process, the realization of the breaking of the strings in this composition is found at the end of the codetta as the closing of the work. Meanwhile, creative processing which is carried out based on the word "Pedhot" (break) itself, is used in the arrangement of musical forms that are arranged intermittently, namely from one semifrase to the next semifrase in stages until the entire semifrase is composed completely. The purpose of this study is to determine the creative process in composing "Pedhot" musical compositions, as well as being one of the references and information on how the process of a musical composition is created. Although music composition is closely related to its subjectivity, writing it in a scientific article will bring a musical composition to the area of ??objectivity based on scientific corridors.